Loyalty, dissent, and betrayal : modern Lithuania and East-Central European moral imagination - Donskis, Leonidas (On the boundary of two worlds, 2005)
Loyalty and betrayal are among key concepts of the ethic of nationalism. Marriage of state and culture, which seems the essence of the congruence between political power structure and collective identity, usually offers a simple explanation of loyalty and dissent. Loyalty is seen as once-and-for-all commitment of the individual to his or her nation, whereas betrayal is identified as a failure to commit him or herself to a common cause or as a diversion from the object of political loyalty and cultural/linguistic fidelity. For conservative or radical nationalists, even social and cultural criti.